Identification of mechanisms regulating the intra cellular concentration of rifampicin in Mycobacterium Tuberculosis - De Vos, Margaretha (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.